493 Increased Utilization of Healthcare Services in Children with Craniosynostosis. (1st April 2022) - Colon, Gabriela R.; Jin, Michael C.; Grant, Gerald A.; Prolo, Laura M.
Abstract : INTRODUCTION: Craniosynostosis is a condition characterized by the premature fusion of at least one cranial suture. While evidence suggests that both syndromic and nonsyndromic patients may benefit from developmental, behavioral, and mental health support, data on utilization of healthcare services is lacking. METHODS: The Optum Clinformatics® DataMart database was queried to identify 1340 patients with craniosynostosis. Long-term utilization of mental health care, rehabilitation therapies, and other medical services up to age six was calculated. Rates of utilization were compared to healthy controls (n = 1577) and children with plagiocephaly (n = 1249). RESULTS: Mental health care was utilized more frequently in craniosynostosis patients (8.1%) compared to plagiocephaly (5.0%, p=0.0020) and healthy controls (2.9%, p<0.0001) . Physical, occupational and speech therapy were more frequently used by plagiocephaly than craniosynostosis patients (14.1% vs. 11.2%, p = 0.0283), which was significantly higher than use by controls (11.2% vs. 3.9%, p<0.0001). Other medical subspecialty services (developmental pediatrics, ophthalmology, optometry and audiology) were utilized by 37.0% of craniosynostosis patients, compared with 20.9% (p<0.0001) and 15.1% (p<0.0001) of plagiocephaly and healthy controls, respectively. Among craniosynostosis patients, utilization was not uniform by age; while ophthalmology utilization did not differ by age (p = 0.1003), mental health care was most commonly used among older children (p = 0.0107). CONCLUSION: In this study, we demonstrate that children with craniosynostosis utilize mental health care, rehabilitation therapies, and other medical subspecialty services at a higher rate than controls. While surgical correction may be considered an isolated event, these children should be monitored for developmental and mental health support longitudinally. Future work should explore risk factors driving utilization, including suture involvement, repair type, and comorbidities.